Gender-Based Differentials in Consumer Awareness of Neuromarketing Techniques: An Empirical Study in the Udaipur Hotel Industry - Nisha Tamboli; Dr. Rekha Kumawat (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study investigates gender-based differences in consumer awareness of neuromarketing techniques within the hospitality sector of Udaipur, Rajasthan. With increasing emphasis on consumer-centric strategies, neuromarketing has emerged as a powerful tool to decode consumer behavior by employing technologies like eye-tracking, EEG, and facial coding. The research aims to evaluate whether male and female consumers significantly differ in their awareness and perception of such neuromarketing interventions applied in the hotel industry. Drawing responses from 343 valid participants—178 male and 165 female—this empirical investigation uses descriptive and inferential statistics, including ANOVA, to determine patterns in awareness levels. The analysis reveals a near-equal gender distribution, ensuring representativeness across the dataset. While descriptive statistics suggest only minor differences in mean awareness scores across various neuromarketing-related statements, the ANOVA results provide deeper insight. Four out of six statements reflected statistically significant gender-based differences in perception, while two showed no such significance. Notably, females exhibited slightly higher awareness in areas like marketing tactics and consumer preference tracking, while males aligned closely in areas like technological usage and behavioral understanding. The findings reject the null hypothesis and affirm that gender influences neuromarketing awareness in the Udaipur hotel industry. This study contributes to the emerging discourse on consumer psychology and marketing innovations in Tier-2 tourism hubs. The implications are crucial for hotel marketers seeking to personalize strategies effectively. The paper also offers recommendations for marketers, academicians, and policymakers, along with reflections on limitations and directions for future research.